Inbreeding depression in one of the last DFTD-free wild populations of Tasmanian devils - Rebecca M. Gooley; Carolyn J. Hogg; Samantha Fox; David Pemberton; Katherine Belov; Catherine E. Grueber (PeerJ, 2020)
Background Vulnerable species experiencing inbreeding depression are prone to localised extinctions because of their reduced fitness. For Tasmanian devils, the rapid spread of devil facial tumour disease (DFTD) has led to population declines and fragmentation across the species’ range. Here we show that one of the few remaining DFTD-free populations of Tasmanian devils is experiencing inbreeding depression. Moreover, this population has experienced a significant reduction in reproductive success over recent years. Methods We used 32 microsatellite loci to examine changes in genetic diversity and inbreeding in the wild population at Woolnorth, alongside field data on breeding success from females to test for inbreeding depression. Results Wefound that maternal internal relatedness has a negative impact on litter sizes. The results of this study imply that this population may be entering an extinction vortex and that to protect the population genetic rescue should be considered. This study provides conservation managers with useful information for managing wild devils and provides support for the “Wild Devil Recovery Program”, which is currently augmenting small, isolated populations.